Astounding Fibro Lipoma of Spermatic Cord: A Diagnostic Dilemma. (6th September 2021) - Rohit, Gupta; Hariprasad, Chinniahnapalaya Pandurangaiah; Bharti, Shreekant; Kumar, Anil; Paswan, Shiv Shankar; Vikram, Surya; Anand, Atul; Anto, Jijo
Abstract : Background . Fibro lipoma of the spermatic cord is a very rare tumor with few cases reported in literature. Atypical presentation and site of swelling mystifies the diagnosis and creates bewildering situation intraoperatively. Case Summary . A 30-year-old farmer presented with an elastic firm nonreducible, nontender swelling at inguinoscrotal region with positive cough impulse and history of laparoscopic inguinal hernia repair 3 years ago. Ultrasonography of the swelling revealed a heteroechoic lesion of size 7 × 6 centimeter with probable features of lipoma or desmoid. Fine needle aspiration drawn in consideration of the diagnostic dilemma reported a benign lipomatous swelling which on final histopathology turned out to be a fibro lipoma of size 7 × 6 × 5  cm. Conclusion . Considering the age and presentation of the patient, it was astonishing. It provided an insight to the occurrence of fibro lipoma even in younger age group which in fact is the first case of its kind as per best of our knowledge. Malignancy should be ruled out in such cases, and complete excision is the treatment of choice.